Case Report: A Case of Acute T Lymphoblastic Leukemia With Mixed Infection of Lethal Invasive Mucormycosis and Multi-Drug Resistant Bacteria - Cui, Qingya; Dai, Haiping; Wu, Depei; He, Jun; Xu, Yang; Tang, Xiaowen; Xu, Jie (Frontiers in Medicine, 2022)
Pulmonary mucormycosis (PM) is a rare and life-threatening fungal infection. Here, we reported a case of an acute T lymphoblastic leukemia patient with mixed infections of lethal invasive Mucormycosis and multi-drug resistance (MDR) bacteria. After receiving anti-infection drugs to control his fever, the patient was treated with induction chemotherapy. Nevertheless, the malignant hematological disease was poorly controlled by the chemotherapy and the patient demonstrated severer infection symptoms. Although the results of multiple β-D-Glucan (G) and Galactomannan (GM) tests remained negative, we were able to detect several pathogenic infections using the metagenomic next-generation sequencing (mNGS). Particularly, mNGS identified the infection of Malassezia pachydermum, Mucor racemosus, and Lauteria mirabilis from the peripheral blood and local secretion samples. The Mucor and bacterial infections were further confirmed using multi-site and repeated fungal and bacterial culturing assays, respectively. Despite that we have adjusted the anti-infection therapy according to the diagnostic results, the patient’s blood disease and infection symptoms were not alleviated. Additionally, we could not confirm the MDR Acinetobacter baumannii infection until the seventh trial of the peripheral blood catheter culturing assay. Due to the deteriorating disease conditions, the patient's family members decided to withdraw from further treatments. Overall, mNGS could potentially facilitate the diagnosis of Mucormycosis by providing clinical and therapeutic clues in addition to the conventional diagnostic approaches. It is also crucial to consider the malignant hematological conditions and adopt multi-approach repeated tests, thus providing early and timely diagnosis and treatment of PM.